Evaluation of Front Line Demonstrations on Gram in Arid Zone - Singh, Bhagwan; Saxena, Anurag (Annals of Arid Zone, 2018)
The study was carried out during rabi seasons of 2014-15 and 2015-16 in seven villages of Barmer, Jaisalmer and Jodhpur districts of Rajasthan to evaluate the front line demonstrations on gram conducted by ICAR-Central Arid Zone Research Institute, Jodhpur. The data were collected from 45 farmers. The findings of the study results revealed that improved technology recorded a mean yield of 1517 kg ha-1 which was 22.4% higher than the yield obtained by farmers’ practices (1230 kg ha-1). The higher net returns (Rs. 47223 ha-1) and benefit: cost ratio of 1.52 was obtained with improved technologies in comparison to farmer’s practices (Rs. 38354 and 1.33 correspondingly). Key words: Gram, front line demonstration, extension gap, technology gap, technology index.